دور البرامج الإصلاحية في تأهيل وإصلاح النزلاء دراسة ميدانية في سجن مدينة اللاذقية - عقيـل, أديـب; برقـاوي, هناء; إسماعيل, رنـدا (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يعتبر تأهيل النزلاء وإعدادهم للعودة إلى مجتمعاتهم أشخاصاً صالحين الهدف الأساسي للسجون والسياسة العقابية في مجملها. ومن هنا ظهرت الاهتمامات التي تسعى إلى رصد أثر بيئة المؤسسة الإصلاحية على النزلاء ومبلغ ما تحققه من إنجاز بغية تحقيق الأهداف المنشودة من برامجها الوقائية والإصلاحية التي تصب في صالح تحقيق الاندماج الاجتماعي للنزيل في بيئة المؤسسة المودع بها، ثم بعد ذلك في مجتمعه الخارجي، وأن تقنع النزيل أن ينبذ المفاهيم والمواقف التي أدت به إلى الانحراف، وتبين مواقف سليمة تمتلك تفكيره وتقوده إلى الطريق السليم. وبذلك يمكن القول إن المؤسسات العقابية أصبحت إحدى الوسائل الهامة التي يتمكن من خلالها المجتمع من المحافظة على أفراده من هؤلاء الخارجين على القانون والقيم السائدة في المجتمع، وفي الوقت نفسه محاولة إصلاحهم وتأهيلهم. The rehabilitation and preparation of prisoners to come back to their societies as good people is considered the main goal for prisons and punitive policy in general. Hence, interests have emerged, aiming at charting the effect of the environment of reformist establishment on prisoners and how much achievement can it realizes in order to achieve the goals wanted from its reformist and protective programs that come down in favor of achieving the social integration of the prisoner in the environment of the establishment he is committed to, and in his society afterwards, convincing the prisoner to carry out the concepts and situations that led him to deviate, and showing sound situations that seize his thinking and guide him to the right way. We can, therefore, say that penal establishments have become one through which society rehabilitates the lawbreakers.